Fracture toughness and color change of Nanohybrid resin composites in dry and wet conditions up to 60 days - Seyyede Fateme Basri; Rafat Bagheri; Maryam Sadat Tavangar (Tehran University of Medical Sciences, 2018)
Background and Aims: Fracture and color change are among the most common causes of clinical failure of resin composite restorations. Therefore, this study aimed to examine the fracture toughness and color changes of 3 Nano-hybrid resin composites in dry and wet conditions. Materials and Methods: Three resin composites were studied. A total of 36 rectangular specimens were prepared for each material, randomly divided into 2 groups, and stored at 37°C dry or soaked in distilled water. In each group, the specimens were subdivided into three groups (n=6) and stored for 1, 7, and 60 days. After each time interval, the specimens were tested for the fracture toughness and loaded at a cross-head speed of 0.5mm/min using a universal testing machine. The baseline and final color measurement was recorded for each specimen using a spectrophotometer. The collected data was analyzed using ANOVA and Kruskal-Wallis tests. Results: After 60 days, the mean value of fracture toughness was lower in the wet condition compared to that of dry condition. However, it was not significantly different except for aura Bulkfil (P=0.001). Color change was significantly different for Tetric Evoceram and aura with a greater value in the wet condition compared to that of dry (P=0.004). The greatest color stability was found for aura and the least for Tetric Evoceram. Conclusion: In this study, most of the materials stored in a dry condition showed a greater fracture toughness and color change.